2019
DOI: 10.1177/1558925019865260
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the removal of reactive golden yellow SNE dye by cross-linked cationic starch and its adsorption properties

Abstract: In this study, cross-linked cationic starch was synthesized with corn starch as a raw material, epichlorohydrin as a cross-linked agent, and 3-chloro-2-hydroxypropyl trimethylammonium chloride as a cationic etherification agent, respectively, and it was characterized by X-ray photoelectron spectroscopy, X-ray powder diffraction, scanning electron microscopy, and thermogravimetry. The X-ray photoelectron spectroscopy results showed that cationic N appeared on the surface of cross-linked cationic starch; that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…A strong peak of 45° was found in both samples, but the intensity was higher in jagung bose than in whole corn. Commonly, corn starch's peak at 45° (2θ angle) was not found [36,[41][42][43]. This peak represented higher crystallinity of jagung bose than that of whole corn.…”
Section: Crystallinitymentioning
confidence: 99%
See 2 more Smart Citations
“…A strong peak of 45° was found in both samples, but the intensity was higher in jagung bose than in whole corn. Commonly, corn starch's peak at 45° (2θ angle) was not found [36,[41][42][43]. This peak represented higher crystallinity of jagung bose than that of whole corn.…”
Section: Crystallinitymentioning
confidence: 99%
“…The morphology of starch granules of whole corn and jagung bose was in accordance with another report. The corn starch granules were polygonal, with a high degree of regularity and a smooth surface [42]. Perera et al [41] reported that starch granules from normal and waxy corn displayed angular or spherical shapes.…”
Section: Starch Granule Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…The first stage of mass loss occurred in the temperature range 37C -117C with the maximum peak at 71.7C and it is related to the moisture evaporation [28,29]. The second stage is occurred in the temperature range 255C -349C, with the maximum peak at 309C and it is associated with a thermal degradation of starch [28,30]. The TG curve (Figure 3a) showed that the thermal decomposition begun at lower temperature for ambroxol in binary mixture with starch compared to pure drug.…”
Section: Figurementioning
confidence: 99%
“…4,5 The textile industry is responsible for a significant portion of all water and air pollution, a large part of which is due to inadequate waste disposal of chemical materials and toxic metals that traditional production processes still use extensively. 6,7 As a result of this type of scenario, the World Commission on Environment and Development (WCED) has highlighted the importance of present and future generations to effusively seek sustainable development through cleaner technologies. These expectations are present in the textile sector.…”
Section: Introductionmentioning
confidence: 99%